Is bis(trifluoromethylsulfonyl)amide an innocent anion? X-ray structure data and DFT calculations. - Illner, Peter; Puchta, Ralph; Heinemann, Frank Wilhelm; van Eldik, Rudi (Dalton Transactions, 2009)
The coordinative behaviour of the bis(trifluoromethylsulfonyl)amide (NTf2-) anion was studied in terms of its interaction with the labile [Pd(terpyridine)Cl]Cl complex. Among various attempts to coordinate NTf2- to the Pd(II) centre, the complexes [Pd(terpyridine)NO3]NTf2 and [Pd(terpyridine)H2O](NTf2)2 were isolated and characterized. The crystallographic data for these complexes are presented and the possible coordination of the NTf2- anion to the metal centre is discussed in reference to DFT predictions.